2007
DOI: 10.1002/zaac.200700090
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Crystal Structure of Novel Mixed Bridged Trinuclear Oxo‐Centered Iron(III), Chromium(III) Complexes Containing Terminal Unsaturated Carboxylato and Acrylic Acid Dimer Anion Ligands

Abstract: Three new oxo-centered trinuclear mixed-bridged carboxylate complexes with terminal unsaturated ligands (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…We suggest that the l 3 -oxygen atom comes from atmospheric molecular oxygen, which is in agreement with results found by Zacchini and co-workers for the compound 6 (DMF)(THF) 2 [37]. In contrast to the literature reports the iron(III) or iron(II) starting species was a low valence iron species (Fe I Fe I or all-Fe 0 ) [38,39].…”
Section: Bond Lengths (Pm)supporting
confidence: 92%
“…We suggest that the l 3 -oxygen atom comes from atmospheric molecular oxygen, which is in agreement with results found by Zacchini and co-workers for the compound 6 (DMF)(THF) 2 [37]. In contrast to the literature reports the iron(III) or iron(II) starting species was a low valence iron species (Fe I Fe I or all-Fe 0 ) [38,39].…”
Section: Bond Lengths (Pm)supporting
confidence: 92%
“…The observed vibrational frequencies, ν asym (COO) and ν sym (COO), for the carboxylate ligand support the presence of bridging coordinated carboxylates in all the complexes. 15 The presence of ionic nitrate in this complex follows from the IR spectrum through the appearance of a relatively weak band at 1380 cm -1 . 14 For a new series of trinuclear mixed-metal complexes, Cannon et al 2 assigned the IR spectra and identified the vibrational modes of the central M 3 O core.…”
Section: Ir Spectroscopymentioning
confidence: 94%
“…In previous studies, we reported fabrication of some trinuclear oxo-centered complexes with saturated and unsaturated carboxylate ligands [10][11][12][13][14]. In this paper, the syntheses and characterization of mixed-valence and mixed-metal clusters are reported.…”
Section: Introductionmentioning
confidence: 99%